EFFECT OF AQUEOUS EXTRACT OF AVICINNIA MARINA ON MYOCARDIAL CONTRAC- TION OF ISOLATED MAMMALIAN HEART - Ahmed, Shahnaz; Rahman, Atiq-ur- (Biological Sciences - PJSIR, 2004)
Aqueous extract of Avicinnia marina commonly known as mangrove showed a marked inhibitory action on isolated mammalian heart in-vitro. The degree of inhibition was found to be highly dose dependent. A dose of 100 mg/kg caused cardiac arrest for few seconds. The force and magnitude of cardiac contractions were regained to pre-injection level after 1.6-2 min. Pretreatment with atropine was found to have no effect on myocardial contractions. The amplitude of cardiac contractions was reduced slightly after the administration of adrenaline.